Perubahan Orientasi Nilai Budaya Masyarakat Dayak Hibun di Sekitar Perkebunan Kelapa Sawit Parindu Saggau Kalimantan Barat - Arkanudin, Arkanudin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The presence of oil palm plantations causes a reduction in forest area which is the basis for fulfilling life needs, and encourages changes in cultural values. The purpose of the study was to determine changes in cultural values due to the presence of oil palm plantations. Data collection was carried out through observation, interviews, and document research, while analysis was carried out by organizing data, presenting data, and drawing conclusions. The results showed that the cultural values of the Dayak Hibun community around oil palm plantations have not changed much, they still have a mindset and attitude of resignation and satisfaction with problems. In work, they still aim to fulfill the needs of life but are starting to be future-oriented.